AN ANALYSIS OF FLOUTING MAXIMS USED BY THE CHARACTERS IN LUCA MOVIE - Siti Mahmudah; Mansur (Pro-ELLitera, 2024)
Language is a communication tool to convey ideas and information. Sometimes language has a different meaning from the meaning spoken by the speaker. The speakers need to maintain their utterances to make the information that they gave still relevant and accepted by the interlocutor or still on the direction of the talk exchange. Maxims are language rules that govern linguistic interactions. This research focuses on the flouting maxim used by ten characters in Luca movie. This research aimed to find out the types of maxims are flouted by the characters and the reasons for flouting maxims used by the characters in Luca movie. The researcher used descriptive-qualitative to collect the data and assisted with Atlas.ti software for data coding. In analyzing the data the researcher employed Grice, (1975) maxims theory. The finding of this research showed that the ten characters flouted four maxims: flouting the maxim of quality (13), flouting the maxim of quantity (9), flouting the maxim of relevance (11), and flouting the maxim of manner (3). The reasons why the characters flouted the maxim is to cover something up, to convince the listeners, to hide something, to provide further explanation, give additional information, to emphasize certain points, to express expectations, to change the topic, to give unimportant information, to avoid talking about something, to get attention, and to be clear.